Malaria Prophylaxis and Vaccinations Among Turkish International Travelers: National Data, 2011-2016 - Gülay OKAY; Cemal AYAZOĞLU; Osman KAN; Meliha MERİÇ KOÇ; Turan ASLAN (Bezmiâlem Science, 2019)

(untitled)
Objective:The number of international travelers is increasing steadily. As a result, there is also an increase in travel-related infections. There is not enough data on travel vaccinations and prophylaxis in Turkey. The aim of this study is to create awareness and to guide national politics by presenting national data of Turkey.Methods:Travelers who took travel health services (THS) at travel health centers (THC) during 2011-2016 were included in the study. The data in the THC’s record system were examined for age, sex, purpose of travel, duration of stay, country of destination, learning source of THS, vaccinations and malaria prophylaxis.Results:During the study period, 162,023 people took THS. There was a 57% increase in the number of travelers who took THS in 2016 compared to 2011. There was no significant increase in the incidence of THS in Turkish travelers going abroad (0.33% and 0.43%, respectively in 2011 and 2016) (rs=0.36 p=0.47). The most common reason for traveling was business trips (79%), the most visited region was Africa (65.7%). The percentages of yellow fever vaccine, typhoid vaccine and malaria prophylaxis were 86.7%, 28.3%, and 44.7%, respectively.Conclusion:The main reason for travel was business and the most frequent destination was Africa. The number of travelers who took THS in travelers going abroad was very low in our country. It was concluded that awareness of travel-related health risks and preventive measures in the community should be increased.